Students’ Learning Obstacles in Solving Mathematical Proficiency Tasks: A Hermeneutic Phenomenological Study Focused on Algebra - Fardian, Dilham; Suryadi, Didi; Prabawanto, Sufyani (UNNES JOURNAL, 2024)
algebra is a fundamental topic in mathematics, particularly emphasized during the junior high school years as an essential subject. In the context of linear equations in one variable, students often struggle with obstacles in basic algebra including variable degrees, variable concepts, coefficients, and constants. However, proficiency in understanding algebraic concepts is significantly lower compared to other areas and skills. As a consequence, this research aimed to explore students' learning obstacles in solving linear equations in one variable in secondary schools based on mathematical proficiency. The research design using the hermeneutic phenomenological approach. This research is a framework of the Didactical Design Research (DDR). DDR is based on two paradigms: the interpretive and the critical paradigms, and it aims to empower students in the context of generating new knowledge as justified true belief. In this study, the researcher delves into the interpretive paradigm. The research subjects involved 46 seventh-grade secondary school students from five different schools across four distinct provinces in Indonesia. The instruments used were test and non-test. The test was done by giving a diagnostic test about linear equation problems, while interviews used the non-test technique. The data collected were analyzed using the Miles and Huberman model, namely data reduction, data presentation, and drawing conclusions. The study findings revealed that students met three types of obstacles in linear equation material, namely ontogenic obstacle, epistemological obstacle and didactical obstacle. However, students faced limited knowledge to solve mathematics problems in one variable, for instance, solving mathematical operations and making modelling problems from real situations deal with linear equations in one variable. Therefore, future research can focus on developing a Didactical Design to reduce this obstacle.